PEMANFAATAN AI DAN CANVA UNTUK PROMOSI DALAM ECOMMERCE - Endar Nirmala; Sri Mulyati; Ari Mulyoto (Abdi Jurnal Publikasi, 2024)
Artificial Intelligence (AI) and graphic design platforms such as Canva have become important elements in promotional strategies for e-commerce businesses in today's digital age. This community service aims to enable SMK Bina Harapan Ciseeng Bogor students to use AI and Canva technology to increase promotion in the e-commerce sector. The method used is a qualitative approach with in-depth interviews and observations as data collection methods. The results show that there is still a need for an understanding of AI and the use of graphic design platforms. This community service integrates AI and Canva into the learning process for students specializing in retail business at SMK Bina Harapan Ciseeng Bogor for promotional purposes. With individual expertise and collective creativity, more effective and innovative promotional materials can be produced. Through this community service, it can help students prepare for the challenges of an increasingly digitally connected world of work. In addition, by addressing ethical and privacy concerns, schools can ensure that this technology is responsible and sustainable. Community service can provide significant benefits to participating students using AI and Canva for e-commerce promotion. Through this community service, students can produce promotions through videos. The conclusion from this community service is that SMK Bina Harapan Ciseeng Bogor still needs to increase training in the use of the currently developing AI technology and understanding of ethics and privacy policies so that students can develop a full understanding of the ethical implications of using this technology.